Aktivasi Klinker Semen Sebagai Katalis Pada Proses Produksi Biodiesel Dari Minyak Sawit Off Grade - Miftahudin, Dhani Nur; Helwani, Zuchra; Bahri, Syaiful (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Clinker cement is a solid material activated by calcinations method. The optimum condition studied by a variation of calcinations time. The catalyst with highest activity is obtained when the calcinations time is 5 hours and calcinations temperature is 700 °C with transesterificationreaction conditions are a molar ratio of methanol/oil 6:1, catalyst dosage of 2% y weight, temperature of 70 °C for 2 hours with yield biodiesel result reached 84,26%. CaO, SiO2, 2CaO.SiO2 and 3CaO.SiO2 materials found in the catalyst thrugh x-ray diffraction (XRD) analysis and specific surface area of catalyst is 25,497 m2/g through Brunauer-Emmett-Teller(BET) analysis. Some of metil ester such as methyl palmitate, methyl oleate, methyl stearic, methyl myristate, and methyl laurate are found through Gas Chromatography-MassSpectrometry (GC-MS) analysis.Keywords: biodiesel, calcium oxide, catalysts, cement clinker, transesterification.